Students’ Perception on Online Learning Experience During Pandemic (Covid-19) - Misbah Misbah; Yasmine Khairunnisa; Dewi Dewantara; Surya Haryandi; Desy Purwasih; Nurlaela Muhammad; Khaerus Syahidi; Mohd Ali Ibrahim (STKIP Singkawang, 2023)
This study aimed to analyze students’ perception about their experience in online learning using blended learning in Physics course. The sample was 101 undergraduate students of Physics education who completed the questionnaire which consisted of 34 questions in Likert scale. The data were analyzed using a semi-explorative approach and the results showed that most of the students thought that the lecturer's teaching methods were good and supported by good facilities. However, students have many assignments and do not feel any improvement in skills. Generally, students' perceptions varied influenced by the Appropriate Workload Scale (AWS) and the Appropriate Assessment Scale (AAS) which were explained by 60.911% of the variation.